2011
DOI: 10.7249/wr889
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Health of Older Indians: Individual and Geographic Determinants of Female Disadvantage

Abstract: India is experiencing a rapid demographic and epidemiologic transition. Among a growing aging population, non-communicable diseases, including dementia, are increasingly prevalent, but our understanding of cognitive health is quite limited. Recent studies suggest that women in developed countries perform as well or better than men on cognitive functioning tests, though research from developing countries shows the opposite. This gender disparity in developing settings may be attributable to that fact that women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…This finding is in line with other research on cognition and aging in LMICs that has found substantial gender differentials in cognitive decline (Lee et al, 2014, 2011; Lei et al, 2014; Maurer, 2011; Zhang, 2006). Despite differences in levels, CH has similar associations with well-being, mental health, and physical health outcomes for both men and women.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in line with other research on cognition and aging in LMICs that has found substantial gender differentials in cognitive decline (Lee et al, 2014, 2011; Lei et al, 2014; Maurer, 2011; Zhang, 2006). Despite differences in levels, CH has similar associations with well-being, mental health, and physical health outcomes for both men and women.…”
Section: Discussionsupporting
confidence: 92%
“…For cognitive ability, LASI administered tests for word recall (both immediate and delayed), a modified version of the Min-Mental State Exam, and serial 7s (see Lee et al, 2011, for a comprehensive description). We create a summary index for these cognitive tests, ranging from 0 to 32.…”
Section: Datamentioning
confidence: 99%
“…Newer versions of the Hindi MMSE have been sometimes used by some researchers (Tiwari et al, 2009). A similarly adapted cognitive screening tool has been used in the important Indian epidemiological study on agingthe Longitudinal Aging Study in India (Lee et al, 2011).…”
Section: How Do Our Findings Relate To Other Studies?mentioning
confidence: 99%
“…It was pretested in the Indian population and has since been used to study health, demography, family, social activities, pre-retirement health behavior, work, pension, and cognition. A cognitive screen was used to assess episodic memory (immediate and delayed word recall) and global cognitive function (date, name of prime minister, reverse counting from 20, and serial sevens) (Lee et al, 2011). Although the screen itself had not been validated prior to the test, many of its items have been used in India earlier (Ganguli et al, 1996;Langa et al, 2008;Mathuranath et al, 2007;Tiwari et al, 2009).…”
Section: Introductionmentioning
confidence: 99%